Chloride ingress in de-icing salt-exposed bridge: Numerical modeling and field investigations - Samaneh Khani; David Conciatori; Luc Chouinard; Benoit Fournier; Mohammad Khaleghi Esfahani; Abdoul S. Bah; Xuande Chen (Case Studies in Construction Materials)
This research focuses on assessing the durability of various components of an onshore section of the Original Champlain Bridge in Montreal, specifically in relation to chloride ingress from de-icing salting operations. Chloride penetration in both the original and repaired concrete are both numerically modelled and measured. The transport characteristics of repaired and original parts of the concrete were determined using non-destructive air permeability tests and used in the TransChlor® to predict chloride ingress into the air-exposed repaired sections and underlying unrepaired sections over the service life of the bridge. By selecting appropriate boundary conditions, and historical climatic data, the predicted chloride profiles are shown to be a close match to core sample data from both the repaired and unrepaired sections of structural elements. This research proposes a blind a-priori prediction method for analyzing and predicting chloride ingress in ageing concrete structures as opposed to a-posteriori predictions made by matching chloride profiles obtained from cores, which is a common practice in the literature. Furthermore, it was clearly demonstrated that cathodic protection is effective in preventing chloride ingress into concrete. However, the ability to predict chloride ingress in the presence of cathodic protection was identified as a gap in current chloride ingress models such as TransChlor®, and an objective for future research.